Talent management ecosystem in the 10 Malaysia Plan: Key success factor for the new economic model - Baharin, Izdihar; Abdullah, Azrai; Jantan, M. Hafiz (2011)
Malaysia today is in the crossroad of whether to remain as a middle income nation or move up the ladder as a high income country. Faced with slower GDP and export growth, coupled with declining FDI and productivity Malaysia desperately needs a new growth model in order to achieve the targets of Wawasan 2020. Malaysia needs to rely more on productivity and innovation to drive her economic growth and talent management had been identified as the key success factor for the 10MP. The successful implementation of the 10MP is paramount to the success of the NEM.